PARADIGMA AKUNTASI SYARIAH DALAM PERSPEKTIF MAQASHID SYARIAH DAN TAFSIR MAQASHIDI - Hamdani, Hamdani (Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ngabar Ponorogo, Indonesia, 2020)
Accounting reporting that is only guided by the conventional economic system and only concerned with profit, has an impact on the economic crisis and certain community misery. Islamic economics which was pioneered by contemporary scholars compiled an economic reporting system that prioritized benefit, transparency, and justice in accounting reporting. Conceptually, this article discusses the sharia accounting paradigm according to the perspective of maqashid sharia and tafsir maqashidi. The position of the maqashid sharia regarding the study of Islamic accounting is divided into five phases, namely guarding religion, guarding the soul, maintaining reason, guarding descent, and safeguarding property. In this case, the tafsir maqashidi is very relevant to understanding the text about maqashid sharia because, first, in the tafsir maqashidi the maqashid sharia approach is discussed from the perspective of Islamic law. Second, maqashid sharia is understood as a religious manhaj.